Extremely-low-temperature-based composite heat-sensitive material with lanthanum manganate core-shell structure coated with double perovskite solid solution and preparation method of extremely-low-temperature-based composite heat-sensitive material
By using a double perovskite solid solution coated with lanthanum manganate core-shell structure composite thermosensitive material in low-temperature NTC thermistor, the problem of narrow temperature measurement interval of the existing low-temperature NTC thermistor is solved, and 10K is achieved The full coverage temperature measurement capability of up to 300K improves the performance and application range of the material.
Patent Information
- Application Number
- CN202311677486.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-06
- Publication Date
- 2025-02-18
AI Technical Summary
The temperature measurement range of existing low-temperature NTC thermistors is narrow, which limits its application range, and traditional preparation methods may lead to problems such as limited measurement temperature range and low repeatability.
The double perovskite solid solution coated lanthanum manganate core-shell structure composite thermal-sensitive material was prepared by sol-gel method and ultrasonic-assisted method, and the coating amount was adjusted to achieve full coverage from an extremely low temperature zone from 10K to 300K to room temperature.
A wide range of temperature measurement capabilities from extremely low temperature zones to room temperature is achieved, improving the performance and application range of materials, and avoiding the problems of limited measurement range and low repeatability in traditional methods.
Smart Images

Figure CN119462147A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of thermosensitive materials, and specifically relates to a composite thermosensitive material with a core-shell structure of double perovskite solid solution coated with lanthanum manganate based on an ultra-low temperature and a preparation method thereof. By adjusting the coating amount, full coverage from the ultra-low temperature range of 10K to 300K to room temperature is achieved. Background Art
[0002] Negative temperature coefficient thermistors are widely used in temperature sensing, protection of electronic components, and suppression of surge current due to their small size, low cost, and fast response. With the rapid development of science and technology and social economy, cryogenic technology has received more and more attention. There is a huge demand for cryogenic measurement and control in large scientific equipment, quantum communication, deep space exploration, and cryogenic semiconductor electronics. In addition, there is also a huge demand for cryogenic measurement and control in military and astronomical observation. The ultra-low temperature NTC thermistor has a wide range of application prospects in the above fields due to its advantages.
[0003] There are many types of low-temperature sensors, mainly including diode type, negative temperature coefficient (NTC) thermistor type, thermocouple type, etc. Negative temperature coefficient thermistors have become the mainstream of designing new low-temperature temperature sensors due to their high sensitivity, good interchangeability, fast response, high reliability, small size and low price. In recent years, scientific and technological workers have conducted some explorations on low-temperature NTC thermistors, but there is a general problem of narrow temperature measurement range, which limits the application of low-temperature NTC thermistors. Therefore, it is very important to study an ultra-wide temperature range NTC thermistor material that includes an extremely low temperature zone.
[0004] Core-shell structure composite ceramics have the advantages of widening the temperature range of measurement and control and achieving complementary performance of different materials, and have received extensive attention from researchers in recent years. In addition, traditional NTC ceramic preparation methods (such as doping and substitution) may lead to problems such as limited measurement temperature range and low repeatability, while solid solution materials can effectively avoid these problems. By adjusting the component ratio of the solid solution, the performance of the material can be effectively improved. Summary of the invention
[0005] The purpose of the present invention is to provide a composite thermosensitive material with a core-shell structure of lanthanum manganate coated with a double perovskite solid solution based on an extremely low temperature and a preparation method thereof, wherein a La-Mn-O-based core material and a (Zn-Bi-Ti-O)-(Ba-Sr-Ti-O)-based composite shell material are prepared by a sol-gel method, and an ultrasonic-assisted method and different dispersants are used to coat the (Zn-Bi-Ti-O)-(Ba-Sr-Ti-O)-based composite sol on the surface of the La-Mn-O-based core material to form a composite core-shell structure material system. The electrical performance of the material system is tested, and its electrical performance parameters are B 100K / 200K =781-1464K,ρ 100K=243-3851Ω·cm. This material system can be used for temperature measurement in the extremely low temperature range of 10-300K.
[0006] In order to achieve the above object, the present invention adopts the following technical solutions:
[0007] A double perovskite solid solution coated lanthanum manganate core-shell structure composite thermosensitive material based on an extremely low temperature, wherein a double perovskite solid solution (Zn-Bi-Ti-O)-(Ba-Sr-Ti-O)-based composite sol is coated on the surface of a La-Mn-O-based core material to form a core-shell structure powder material, wherein the coating amount is x% La-Mn-O@(100-x)% (Zn-Bi-Ti-O)-(Ba-Sr-Ti-O);
[0008] Electrical performance parameters are B 100K / 200K =781-1464K,ρ 100K =243-3851Ω·cm.
[0009] The present invention also provides a method for preparing a composite thermosensitive material having a core-shell structure of lanthanum manganate coated with a double perovskite solid solution based on an extremely low temperature, the preparation method comprising:
[0010] a. Weigh analytically pure lanthanum salt and manganese salt as raw materials according to molar percentage, wherein the molar percentage of lanthanum salt: manganese salt = 4% to 100%: 4% to 100%, dissolve in deionized water to prepare a 0.04 to 3 mol / L ion mixed solution;
[0011] b. Weigh a complexing agent and add it to the ion mixed solution of step a, wherein the molar percentage of complexing agent: metal ion = 30% to 500%: 100% to 800%;
[0012] c. Stirring the mixed solution obtained in step b at 80-120° C. for 3-6 h to form a La-Mn-O-based sol, drying the sol at 170-250° C. for 25-45 h to obtain a xerogel, and grinding the xerogel for 5-8 h to obtain a powder;
[0013] d. The powder obtained in step c is placed in a bell furnace and thermally decomposed at a temperature of 600-1000° C. for 5-8 hours for pre-calcination, and then taken out and ground for 5-8 hours to obtain a La-Mn-O-based powder;
[0014] e. Preparation of shell materials:
[0015] A Ba-Sr-O solution was prepared by a sol-gel method, wherein strontium salt and barium salt were weighed in a molar ratio of 1:1 and dissolved in an ethylene glycol solution to form a Ba-Sr-O matrix solution;
[0016] A Zn-Bi-O solution was prepared by a sol-gel method, wherein bismuth salt and zinc salt were weighed and dissolved in an ethylene glycol solution in a molar ratio of 2:1 to form a Zn-Bi-O matrix solution;
[0017] The obtained Zn-Bi-O matrix solution and Ba-Sr-O matrix solution are mixed uniformly, wherein the percentage of Zn-Bi-O matrix solution:Ba-Sr-O matrix solution = 1% to 50%:1% to 50%, and magnetically stirred and heated to 80 to 120° C. to form a uniform transparent solution 1, which is set aside;
[0018] f. Weigh 0.01-3 mol of tetrabutyl titanate and dissolve it in anhydrous ethanol, and drop 0.01-0.3 mol of acetylacetone into it, stir it thoroughly to form a uniform transparent yellow solution 2, and set it aside;
[0019] g. Mix the solution 1 obtained in step e and the solution 2 obtained in step f uniformly, weigh a complexing agent and add it to the mixed solution, stir at a temperature of 80-120° C. until a (Zn-Bi-Ti-O)-(Ba-Sr-Ti-O)-based composite sol is formed, and add an appropriate amount of dispersant to the composite sol for standby use; wherein the molar percentage of complexing agent: metal ion = 30%-500%: 100%-800%;
[0020] h. The La-Mn-O-based powder obtained in step d is ultrasonically dispersed for 50 to 150 minutes by an ultrasonic-assisted method, and a proper amount of dispersant is added thereto, and then dropwise added into the (Zn-Bi-Ti-O)-(Ba-Sr-Ti-O)-based composite sol in step g, and stirring is continued for 3 to 6 hours. After the (Zn-Bi-Ti-O)-(Ba-Sr-Ti-O)-based composite sol is fully coated on the surface of the La-Mn-O-based powder to form a material with a core-shell structure, the powder is placed in a blast drying oven and dried at a constant temperature of 170 to 250° C. for 25 to 45 hours to obtain a dry gel, wherein the percentages of La-Mn-O:(Zn-Bi-Ti-O)-(Ba-Sr-Ti-O)=1%-99%:99%-1%;
[0021] i. Thermally decompose the dry gel obtained in step h at a temperature of 800-1000° C. for 5-8 h to obtain a composite core-shell structure powder material of x% La-Mn-O@(100-x)% (Zn-Bi-Ti-O)-(Ba-Sr-Ti-O), which is a composite thermosensitive material based on an extremely low temperature double perovskite solid solution coated with a lanthanum manganate core-shell structure.
[0022] Preferably, the lanthanum salt is lanthanum acetate, lanthanum nitrate or lanthanum oxalate, and the manganese salt is manganese acetate, manganese nitrate or manganese oxalate.
[0023] Preferably, the complexing agent is citric acid or ethylenediaminetetraacetic acid or malic acid or malonic acid.
[0024] Preferably, the strontium salt is strontium acetate, strontium nitrate or strontium oxalate; and the barium salt is barium acetate, barium nitrate or barium oxalate.
[0025] Preferably, the bismuth salt is bismuth acetate, bismuth nitrate or bismuth oxalate; and the zinc salt is zinc acetate, zinc nitrate or zinc oxalate.
[0026] Preferably, the dispersant is polyvinyl alcohol, polyacrylic acid or polyacrylamide.
[0027] The present invention discloses a composite thermosensitive material with a core-shell structure of lanthanum manganate coated with a double perovskite solid solution based on an ultra-low temperature and a preparation method thereof. The sol-gel method and the ultrasound-assisted method are used to prepare a La-Mn-O-based core material and a (Zn-Bi-Ti-O)-(Ba-Sr-Ti-O)-based composite sol. The method mainly comprises: (1) coating the double perovskite solid solution (Zn-Bi-Ti-O)-(Ba-Sr-Ti-O)-based composite sol on the surface of the La-Mn-O-based core material for the first time to form a core-shell structure. Moreover, compared with the coating of a single perovskite structure, the double perovskite phase solid solution can introduce more ions to achieve a synergistic effect of multiple ions, thereby better optimizing the performance. (2) By effectively regulating the interface of (Zn-Bi-Ti-O)-(Ba-Sr-Ti-O) and La-Mn-O, the coating ratio can be accurately controlled, thereby further realizing the preparation of high-performance thermosensitive ceramic materials and controllable and adjustable performance. The x%La-Mn-O@(100-x)%(Zn-Bi-Ti-O)-(Ba-Sr-Ti-O) composite core-shell structure powder material prepared by the present invention can adjust the resistivity and material constant of the thermistor element by changing the ratio of the core to the shell. As the coating ratio of x%La-Mn-O@(100-x)%(Zn-Bi-Ti-O)-(Ba-Sr-Ti-O) changes, its electrical performance parameters are B 100K / 200K =781-1464K,ρ 100K =243-3851Ω·cm. (3) Obtaining extremely low temperature NTC thermistor materials from 10K to 300K, which can meet the measurement and control requirements from extremely low temperature area to room temperature.
[0028] The present invention adopts double perovskite coating. Compared with single perovskite coating, its difficulty lies in precise regulation, that is, controlling the ratio of two substances in double perovskite. The present invention achieves precise regulation of its coating structure through the comprehensive use of multiple additives such as complexing agents and dispersants.
[0029] The present invention achieves lower temperature monitoring in the temperature range, because at extremely low temperatures, the progress of 10K is also a very important breakthrough. The present invention can be from -263°C to room temperature without multiple ratio changes. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 This is a resistance-temperature characteristic curve of the composite core-shell structure material with a coating content of 94% La-Mn-O@6% (Zn-Bi-Ti-O)-(Ba-Sr-Ti-O) according to the present invention. DETAILED DESCRIPTION
[0031] The technical solution of the present invention is described in detail below with reference to the accompanying drawings and embodiments.
[0032] Example 1
[0033] a. Weigh analytically pure lanthanum acetate and manganese acetate as raw materials according to molar percentage, wherein the molar percentage of lanthanum acetate: manganese acetate = 4%:4%, dissolve them in deionized water to prepare a 0.04 mol / L ion mixed solution;
[0034] b. Weigh citric acid as a complexing agent and add it to the mixed solution of step a, wherein the molar percentage of citric acid: metal ion = 500%:800%;
[0035] c. Stirring the mixed solution obtained in step b at 120° C. for 3 h to form a La-Mn-O-based sol, placing the sol in a blast drying oven at 170° C. and drying for 45 h to obtain a xerogel, and grinding for 5 h to obtain a powder;
[0036] d. The powder obtained in step c is placed in a bell furnace and thermally decomposed at a temperature of 600° C. for 4 h for pre-calcination, and then taken out and ground for 5 h to obtain a La-Mn-O-based powder for standby use;
[0037] e. Preparation of shell material: Prepare Ba-Sr-O solution by sol-gel method, weigh 0.5 mol strontium acetate and 0.5 mol barium acetate according to molar percentage and dissolve them in ethylene glycol solution to form Ba-Sr-O matrix solution; prepare Zn-Bi-O solution by sol-gel method, weigh 1.0 mol bismuth acetate and 0.5 mol zinc acetate according to molar percentage and dissolve them in ethylene glycol solution to form Zn-Bi-O matrix solution. Mix the obtained Zn-Bi-O matrix solution and Ba-Sr-O matrix solution uniformly according to molar percentage, wherein the percentage of Zn-Bi-O matrix solution: Ba-Sr-O matrix solution = 47.5%: 47.5%, stir magnetically and heat to 100°C to form a uniform transparent solution 1, and set aside;
[0038] f. Weigh 0.85 mol of tetrabutyl titanate and dissolve it in anhydrous ethanol, and drop 0.01 mol of acetylacetone into it, stir it thoroughly to form a uniform transparent yellow solution 2, and set it aside;
[0039] g. Mix the solution 1 obtained in step e and the solution 2 obtained in step f evenly, weigh citric acid as a complexing agent and add it to the mixture, stir at 120° C. until a (Zn-Bi-Ti-O)-(Ba-Sr-Ti-O)-based composite sol is formed, and add an appropriate amount of polyvinyl alcohol as a dispersant to the composite sol for later use; wherein citric acid: metal ions (0.90 molLa 3+ ,0.90molMn 3+ ,0.01molBi 3+ ,0.005molZn 2+ ,0.045molBa 2+ ,0.045molSr 2+ ,0.095molTi 4+ )'s molar percentage = 500%: 800%;
[0040] h. The La-Mn-O-based powder obtained in step d is ultrasonically dispersed for 50 minutes by an ultrasonic-assisted method, and a proper amount of polyvinyl alcohol is added thereto as a dispersant, and then added dropwise to the (Zn-Bi-Ti-O)-(Ba-Sr-Ti-O)-based composite sol in step g, and stirring is continued for 3 hours. After the (Zn-Bi-Ti-O)-(Ba-Sr-Ti-O)-based composite sol is fully coated on the surface of the La-Mn-O-based powder to form a material with a core-shell structure, the powder is placed in a blast drying oven and dried at a constant temperature of 170° C. for 25 hours to obtain a dry gel, wherein the percentage of La-Mn-O:(Zn-Bi-Ti-O)-(Ba-Sr-Ti-O)=90%:10%;
[0041] i. The dry gel obtained in step h was thermally decomposed at a temperature of 800° C. for 5 h to obtain a 90% La-Mn-O@10% (Zn-Bi-Ti-O)-(Ba-Sr-Ti-O) composite core-shell structure powder material.
[0042] The obtained 90% La-Mn-O@10% (Zn-Bi-Ti-O)-(Ba-Sr-Ti-O) composite core-shell structure powder material was pre-sintered at 800℃ for 3h, ground for 5h, pressed into tablets, cold isostatically pressed, and then sintered at 1300℃ for 3h to obtain a negative temperature coefficient thermistor material. Its parameter B 100K / 200K =1084K;ρ 100K =3578Ω·cm.
[0043] Example 2
[0044] a. Weigh analytically pure lanthanum acetate and manganese acetate as raw materials according to molar percentage, wherein the molar percentage of lanthanum acetate: manganese acetate = 90%:90%, dissolve them in deionized water to prepare a 3 mol / L ion mixed solution;
[0045] b. Weigh ethylenediaminetetraacetic acid as a complexing agent and add it to the mixed solution of step a, wherein the molar percentage of ethylenediaminetetraacetic acid: metal ion = 30%:100%;
[0046] c. Stirring the mixed solution obtained in step b at 80° C. for 6 h to form a La-Mn-O-based sol, placing the sol in a blast drying oven at 250° C. and drying for 25 h to obtain a xerogel, and grinding for 8 h to obtain a powder;
[0047] d. The powder obtained in step c is placed in a bell furnace and thermally decomposed at a temperature of 1000° C. for 8 h for pre-calcination, and then taken out and ground for 8 h to obtain a La-Mn-O-based powder for standby use;
[0048] e. Preparation of shell material: Prepare Ba-Sr-O solution by sol-gel method, weigh 0.5 mol strontium acetate and 0.5 mol barium acetate according to molar percentage and dissolve them in ethylene glycol solution to form Ba-Sr-O matrix solution; prepare Zn-Bi-O solution by sol-gel method, weigh 1.0 mol bismuth acetate and 0.5 mol zinc acetate according to molar percentage and dissolve them in ethylene glycol solution to form Zn-Bi-O matrix solution. Mix the obtained Zn-Bi-O matrix solution and Ba-Sr-O matrix solution uniformly according to molar percentage, wherein the percentage of Zn-Bi-O matrix solution: Ba-Sr-O matrix solution = 5%:5%, stir magnetically and heat to 80°C to form a uniform transparent solution 1, and set aside;
[0049] f. Weigh 0.15 mol of tetrabutyl titanate and dissolve it in anhydrous ethanol, and drop 0.3 mol of acetylacetone into it, stir it thoroughly to form a uniform transparent yellow solution 2, and set it aside;
[0050] g. Mix the solution 1 obtained in step e and the solution 2 obtained in step f evenly, weigh ethylenediaminetetraacetic acid as a complexing agent and add it to the mixed solution, stir at 80° C. until a (Zn-Bi-Ti-O)-(Ba-Sr-Ti-O)-based composite sol is formed, and add an appropriate amount of polyvinyl alcohol as a dispersant to the composite sol for standby use; wherein ethylenediaminetetraacetic acid: metal ions (0.92 molLa 3+ ,0.92molMn 3+ ,0.008molBi 3+ ,0.004molZn 2+ ,0.036molBa 2+ ,0.036molSr 2+ ,0.076molTi 4+ )'s molar percentage = 30%: 100%;
[0051] h. The La-Mn-O-based powder obtained in step d is ultrasonically dispersed for 120 min by an ultrasonic-assisted method, and a proper amount of polyvinyl alcohol is added thereto as a dispersant, and then added dropwise to the (Zn-Bi-Ti-O)-(Ba-Sr-Ti-O)-based composite sol in step g, and stirring is continued for 6 h. After the (Zn-Bi-Ti-O)-(Ba-Sr-Ti-O)-based composite sol is fully coated on the surface of the La-Mn-O-based powder to form a material with a core-shell structure, the powder is placed in a blast drying oven and dried at a constant temperature of 250° C. for 45 h to obtain a dry gel, wherein the percentage of La-Mn-O:(Zn-Bi-Ti-O)-(Ba-Sr-Ti-O)=92%:8%;
[0052] i. The dry gel obtained in step h was thermally decomposed at a temperature of 1000° C. for 5 h to obtain a 92% La-Mn-O@8% (Zn-Bi-Ti-O)-(Ba-Sr-Ti-O) composite core-shell structure powder material.
[0053] The obtained 92% La-Mn-O@8% Ba-Sr-Ti-O composite core-shell structure powder material was pre-sintered at 900℃ for 3h, ground for 5h, pressed into tablets, cold isostatically pressed, and then sintered at 1200℃ for 3h to obtain a negative temperature coefficient thermistor material. Its parameter B 100K / 200K =907K;ρ 100K =937Ω·cm.
[0054] Example 3
[0055] a. Weigh analytically pure lanthanum nitrate and manganese nitrate as raw materials according to molar percentage, wherein the molar percentage of lanthanum nitrate: manganese nitrate = 45%:45%, dissolve in deionized water to prepare a 0.3 mol / L ion mixed solution;
[0056] b. Weigh malic acid as a complexing agent and add it to the mixed solution of step a, wherein the molar percentage of malic acid: metal ion = 200%:300%;
[0057] c. Stirring the mixed solution obtained in step b at 100° C. for 4 h to form a La-Mn-O-based sol, placing the sol in a blast drying oven at 190° C. and drying for 35 h to obtain a xerogel, and grinding for 6 h to obtain a powder;
[0058] d. The powder obtained in step c is placed in a bell furnace and thermally decomposed at a temperature of 800° C. for 6 h for pre-calcination, and then taken out and ground for 6 h to obtain a La-Mn-O-based powder for standby use;
[0059] e. Preparation of shell material: Prepare Ba-Sr-O solution by sol-gel method, weigh 0.5 mol strontium nitrate and 0.5 mol barium nitrate according to molar percentage and dissolve them in ethylene glycol solution to form Ba-Sr-O matrix solution; prepare Zn-Bi-O solution by sol-gel method, weigh 1.0 mol bismuth nitrate and 0.5 mol zinc nitrate according to molar percentage and dissolve them in ethylene glycol solution to form Zn-Bi-O matrix solution. Mix the obtained Zn-Bi-O matrix solution and Ba-Sr-O matrix solution uniformly according to molar percentage, wherein the percentage of Zn-Bi-O matrix solution: Ba-Sr-O matrix solution = 22.5%: 22.5%, stir magnetically and heat to 100°C to form a uniform transparent solution 1, and set aside;
[0060] f. Weigh 1.15 mol of tetrabutyl titanate and dissolve it in anhydrous ethanol, and drop 0.1 mol of acetylacetone into it, stir it thoroughly to form a uniform transparent yellow solution 2, and set it aside;
[0061] g. Mix the solution 1 obtained in step e and the solution 2 obtained in step f evenly, weigh malic acid as a complexing agent and add it to the mixture, stir at 100° C. until a (Zn-Bi-Ti-O)-(Ba-Sr-Ti-O)-based composite sol is formed, and add an appropriate amount of polyacrylic acid as a dispersant to the composite sol for later use; wherein malic acid: metal ion (0.94 molLa 3+ ,0.94molMn 3+ ,0.006molBi 3+ ,0.003molZn 2+ ,0.027molBa 2+ ,0.027molSr 2+ ,0.057molTi 4+ )'s molar percentage = 150%: 300%;
[0062] h. The La-Mn-O-based powder obtained in step d is ultrasonically dispersed for 70 minutes by an ultrasonic-assisted method, and an appropriate amount of polyacrylic acid is added thereto as a dispersant, and then added dropwise to the (Zn-Bi-Ti-O)-(Ba-Sr-Ti-O)-based composite sol in step g, and stirring is continued for 4 hours. After the (Zn-Bi-Ti-O)-(Ba-Sr-Ti-O)-based composite sol is fully coated on the surface of the La-Mn-O-based powder to form a material with a core-shell structure, it is placed in a blast drying oven and dried at a constant temperature of 190° C. for 35 hours to obtain a dry gel, wherein the percentage of La-Mn-O:(Zn-Bi-Ti-O)-(Ba-Sr-Ti-O)=94%:6%;
[0063] i. The dry gel obtained in step h was thermally decomposed at 900° C. for 4 h to obtain a 94% La-Mn-O@6% (Zn-Bi-Ti-O)-(Ba-Sr-Ti-O) composite core-shell structure powder material.
[0064] The obtained 94% La-Mn-O@6% (Zn-Bi-Ti-O)-(Ba-Sr-Ti-O) composite core-shell structure powder material was pre-sintered at 1000℃ for 3h, ground for 5h, pressed into tablets, cold isostatically pressed, and then sintered at 1100℃ for 3h to obtain a negative temperature coefficient thermistor material. Its parameter B 100K / 200K =781K;ρ 100K =243Ω·cm. The resistance-temperature characteristic curve of 94%La-Mn-O@6%(Zn-Bi-Ti-O)-(Ba-Sr-Ti-O) composite core-shell structure material is shown in the figure below. Figure 1 shown.
[0065] Example 4
[0066] a. Weigh analytically pure lanthanum nitrate and manganese nitrate as raw materials according to molar percentage, wherein the molar percentage of lanthanum nitrate: manganese nitrate = 4%:4%, dissolve in deionized water to prepare a 0.8 mol / L ion mixed solution;
[0067] b. Weigh malonic acid as a complexing agent and add it to the mixed solution of step a, wherein the molar percentage of malonic acid: metal ion = 300%:400%;
[0068] c. Stirring the mixed solution obtained in step b at 90° C. for 5 h to form a La-Mn-O-based sol, placing the sol in a blast drying oven at 200° C. and drying for 30 h to obtain a xerogel, and grinding the xerogel for 5 h to obtain a powder;
[0069] d. The powder obtained in step c is placed in a bell furnace and thermally decomposed at 700° C. for 8 h for pre-calcination, and then taken out and ground for 5 h to obtain a La-Mn-O-based powder for standby use;
[0070] e. Preparation of shell material: Prepare Ba-Sr-O solution by sol-gel method, weigh 0.5 mol strontium nitrate and 0.5 mol barium nitrate according to molar percentage and dissolve them in ethylene glycol solution to form Ba-Sr-O matrix solution; prepare Zn-Bi-O solution by sol-gel method, weigh 1.0 mol bismuth nitrate and 0.5 mol zinc nitrate according to molar percentage and dissolve them in ethylene glycol solution to form Zn-Bi-O matrix solution. Mix the obtained Zn-Bi-O matrix solution and Ba-Sr-O matrix solution uniformly according to molar percentage, wherein the percentage of Zn-Bi-O matrix solution: Ba-Sr-O matrix solution = 47.5%: 47.5%, stir magnetically and heat to 90°C to form a uniform transparent solution 1, and set aside;
[0071] f. Weigh 1.65 mol of tetrabutyl titanate and dissolve it in anhydrous ethanol, and drop 0.2 mol of acetylacetone into it, stir it thoroughly to form a uniform transparent yellow solution 2, and set it aside;
[0072] g. Mix the solution 1 obtained in step e and the solution 2 obtained in step f evenly, weigh malonic acid as a complexing agent and add it to the mixture, stir at 90°C until a (Zn-Bi-Ti-O)-(Ba-Sr-Ti-O)-based composite sol is formed, and add an appropriate amount of polyacrylic acid as a dispersant to the composite sol for later use; wherein malonic acid: metal ion (0.96 molLa 3+ ,0.96molMn 3+ ,0.004molBi 3+ ,0.002molZn 2+ ,0.018molBa 2+ ,0.018molSr 2+ ,0.038molTi 4+ )'s molar percentage = 350:400%;
[0073] h. The La-Mn-O-based powder obtained in step d is ultrasonically dispersed for 80 minutes by an ultrasonic-assisted method, and a proper amount of polyacrylic acid is added thereto as a dispersant, and then added dropwise to the (Zn-Bi-Ti-O)-(Ba-Sr-Ti-O)-based composite sol in step g, and stirring is continued for 5 hours. After the (Zn-Bi-Ti-O)-(Ba-Sr-Ti-O)-based composite sol is fully coated on the surface of the La-Mn-O-based powder to form a material with a core-shell structure, it is placed in a blast drying oven and dried at a constant temperature of 190° C. for 35 hours to obtain a dry gel, wherein the percentage of La-Mn-O:(Zn-Bi-Ti-O)-(Ba-Sr-Ti-O)=96%:4%;
[0074] i. The dry gel obtained in step h was thermally decomposed at a temperature of 850° C. for 7 h to obtain a 96% La-Mn-O@4% (Zn-Bi-Ti-O)-(Ba-Sr-Ti-O) composite core-shell structure powder material.
[0075] The obtained 96% La-Mn-O@4% (Zn-Bi-Ti-O)-(Ba-Sr-Ti-O) composite core-shell structure powder material was pre-sintered at 1000℃ for 3h, ground for 5h, pressed into tablets, cold isostatically pressed, and then sintered at 1100℃ for 3h to obtain a negative temperature coefficient thermistor material. Its parameter B 100K / 200K =1104K;ρ 800℃ =2242Ω·cm.
[0076] Example 5
[0077] a. Weigh analytically pure lanthanum oxalate and manganese oxalate as raw materials according to molar percentage, wherein the molar percentage of lanthanum oxalate: manganese oxalate = 95%:95%, dissolve them in deionized water to prepare a 1.5 mol / L ion mixed solution;
[0078] b. Weigh citric acid as a complexing agent and add it to the mixed solution of step a, wherein the molar percentage of citric acid: metal ion = 250%:600%;
[0079] c. Stirring the mixed solution obtained in step b at 110° C. for 5 h to form a La-Mn-O-based sol, placing the sol in a blast drying oven at 210° C. and drying for 40 h to obtain a xerogel, and grinding for 8 h to obtain a powder;
[0080] d. The powder obtained in step c is placed in a bell furnace and thermally decomposed at a temperature of 950° C. for 5 h for pre-calcination, and then taken out and ground for 8 h to obtain a La-Mn-O-based powder for standby use;
[0081] e. Preparation of shell material: Prepare Ba-Sr-O solution by sol-gel method, weigh 0.5 mol strontium oxalate and 0.5 mol barium oxalate according to molar percentage and dissolve them in ethylene glycol solution to form Ba-Sr-O matrix solution; prepare Zn-Bi-O solution by sol-gel method, weigh 1.0 mol bismuth oxalate and 0.5 mol zinc oxalate according to molar percentage and dissolve them in ethylene glycol solution to form Zn-Bi-O matrix solution. Mix the obtained Zn-Bi-O matrix solution and Ba-Sr-O matrix solution evenly according to molar percentage, wherein the percentage of Zn-Bi-O matrix solution: Ba-Sr-O matrix solution = 2.5%:2.5%, stir magnetically and heat to 110°C to form a uniform transparent solution 1, and set aside;
[0082] f. Weigh 0.35 mol of tetrabutyl titanate and dissolve it in anhydrous ethanol, and drop 0.05 mol of acetylacetone into it, stir it thoroughly to form a uniform transparent yellow solution 2, and set it aside;
[0083] g. Mix the solution 1 obtained in step e and the solution 2 obtained in step f evenly, weigh citric acid as a complexing agent and add it to the mixture, stir at 110° C. until a (Zn-Bi-Ti-O)-(Ba-Sr-Ti-O)-based composite sol is formed, and add an appropriate amount of polyacrylamide as a dispersant to the composite sol for later use; wherein citric acid: metal ions (0.98 molLa 3+ ,0.98molMn 3+ ,0.002molBi 3+ ,0.001molZn 2+ ,0.009molBa 2+ ,0.009molSr 2+ ,0.019molTi 4+ )'s molar percentage = 250%: 600%;
[0084] h. The La-Mn-O-based powder obtained in step d is ultrasonically dispersed for 130 minutes by an ultrasonic-assisted method, and a proper amount of polyacrylamide is added thereto as a dispersant, and then added dropwise to the (Zn-Bi-Ti-O)-(Ba-Sr-Ti-O)-based composite sol in step g, and stirring is continued for 3 hours. After the (Zn-Bi-Ti-O)-(Ba-Sr-Ti-O)-based composite sol is fully coated on the surface of the La-Mn-O-based powder to form a material with a core-shell structure, it is placed in a blast drying oven and dried at a constant temperature of 200° C. for 40 hours to obtain a dry gel, wherein the percentage of La-Mn-O:(Zn-Bi-Ti-O)-(Ba-Sr-Ti-O)=98%:2%;
[0085] i. The dry gel obtained in step h was thermally decomposed at a temperature of 950° C. for 8 h to obtain a 98% La-Mn-O@2% (Zn-Bi-Ti-O)-(Ba-Sr-Ti-O) composite core-shell structure powder material.
[0086] The obtained 98% La-Mn-O@2% (Zn-Bi-Ti-O)-(Ba-Sr-Ti-O) composite core-shell structure powder material was pre-sintered at 1000℃ for 3h, ground for 5h, pressed into tablets, cold isostatically pressed, and then sintered at 1100℃ for 3h to obtain a negative temperature coefficient thermistor material. Its parameter B 100K / 200K =1207K;ρ 100K =3473Ω·cm.
[0087] Example 6
[0088] a. Weigh analytically pure lanthanum oxalate and manganese oxalate as raw materials according to molar percentage, wherein the molar percentage of lanthanum oxalate: manganese oxalate = 75%:75%, dissolve them in deionized water to prepare a 3 mol / L ion mixed solution;
[0089] b. Weigh malonic acid as a complexing agent and add it to the mixed solution of step a, wherein the molar percentage of malonic acid: metal ion = 350%:700%;
[0090] c. Stirring the mixed solution obtained in step b at 110° C. for 6 h to form a La-Mn-O-based sol, placing the sol in a blast drying oven at 190° C. and drying for 45 h to obtain a xerogel, and grinding for 5 h to obtain a powder;
[0091] d. The powder obtained in step c is placed in a bell furnace and thermally decomposed at a temperature of 1000° C. for 8 h for pre-calcination, and then taken out and ground for 5 h to obtain a La-Mn-O-based powder for standby use;
[0092] e. Preparation of shell material: Prepare Ba-Sr-O solution by sol-gel method, weigh 0.5 mol strontium oxalate and 0.5 mol barium oxalate according to molar percentage and dissolve them in ethylene glycol solution to form Ba-Sr-O matrix solution; prepare Zn-Bi-O solution by sol-gel method, weigh 1.0 mol bismuth oxalate and 0.5 mol zinc oxalate according to molar percentage and dissolve them in ethylene glycol solution to form Zn-Bi-O matrix solution. Mix the obtained Zn-Bi-O matrix solution and Ba-Sr-O matrix solution uniformly according to molar percentage, wherein the percentage of Zn-Bi-O matrix solution: Ba-Sr-O matrix solution = 17.5%: 17.5%, stir magnetically and heat to 115°C to form a uniform transparent solution 1, and set aside;
[0093] f. Weigh 1.55 mol of tetrabutyl titanate and dissolve it in anhydrous ethanol, and drop 0.2 mol of acetylacetone into it, stir it thoroughly to form a uniform transparent yellow solution 2, and set it aside;
[0094] g. Mix the solution 1 obtained in step e and the solution 2 obtained in step f evenly, weigh malonic acid as a complexing agent and add it to the mixture, stir at 105° C. until a (Zn-Bi-Ti-O)-(Ba-Sr-Ti-O)-based composite sol is formed, and add an appropriate amount of polyacrylamide as a dispersant to the composite sol for later use; wherein malonic acid: metal ions (0.88 molLa 3+ ,0.88molMn 3+ ,0.012molBi 3+ ,0.006molZn 2+ ,0.054molBa 2+ ,0.054molSr 2+,0.114molTi 4+ )'s molar percentage = 450%: 700%;
[0095] h. The La-Mn-O-based powder obtained in step d is ultrasonically dispersed for 140 minutes by an ultrasonic-assisted method, and an appropriate amount of polyacrylamide is added thereto as a dispersant, and then added dropwise to the (Zn-Bi-Ti-O)-(Ba-Sr-Ti-O)-based composite sol in step g, and stirring is continued for 3 hours. After the (Zn-Bi-Ti-O)-(Ba-Sr-Ti-O)-based composite sol is fully coated on the surface of the La-Mn-O-based powder to form a core-shell structure material, it is placed in a blast drying oven and dried at a constant temperature of 250° C. for 45 hours to obtain a dry gel, wherein the percentage of La-Mn-O:(Zn-Bi-Ti-O)-(Ba-Sr-Ti-O)=88%:12%;
[0096] i. The dry gel obtained in step h was thermally decomposed at a temperature of 800° C. for 6 h to obtain a 88% La-Mn-O@12% (Zn-Bi-Ti-O)-(Ba-Sr-Ti-O) composite core-shell structure powder material.
[0097] The obtained 88% La-Mn-O@12% (Zn-Bi-Ti-O)-(Ba-Sr-Ti-O) composite core-shell structure powder material was pre-sintered at 1000℃ for 3h, ground for 5h, pressed into tablets, cold isostatically pressed, and then sintered at 1100℃ for 3h to obtain a negative temperature coefficient thermistor material. Its parameter B 100K / 200K =1464K;ρ 100K =3851Ω·cm.
[0098] The process parameters (such as temperature, time, etc.) of the present invention can realize the method by taking upper and lower limits and interval values, and the embodiments are not listed one by one here.
[0099] Any contents not described in detail in the present invention can be based on the conventional technical knowledge in the art.
[0100] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit the present invention. Although the present invention is described in detail with reference to the embodiments, it should be understood by those skilled in the art that any modification or equivalent replacement of the technical solutions of the present invention does not depart from the spirit and scope of the technical solutions of the present invention and should be included in the scope of the claims of the present invention.
Claims
1. A double perovskite solid solution coated lanthanum manganate core-shell structure composite thermosensitive material based on ultra-low temperature, characterized in that: The double perovskite solid solution (Zn-Bi-Ti-O)-(Ba-Sr-Ti-O)-based composite sol is coated on the surface of the La-Mn-O-based core material to form a core-shell structure powder material, and the coating amount is x%La-Mn-O@(100-x)%(Zn-Bi-Ti-O)-(Ba-Sr-Ti-O); Electrical performance parameters are B 100K / 200K =781-1464K,ρ 100K =243-3851Ω·cm.
2. A method for preparing a composite thermosensitive material having a core-shell structure of lanthanum manganate coated with a double perovskite solid solution at an extremely low temperature, the preparation method comprising: 1) preparing La-Mn-O based powder for standby use; 2) Preparation of shell material: A Ba-Sr-O solution was prepared by a sol-gel method, wherein strontium salt and barium salt were weighed in a molar ratio of 1:1 and dissolved in an ethylene glycol solution to form a Ba-Sr-O matrix solution; A Zn-Bi-O solution was prepared by a sol-gel method, wherein bismuth salt and zinc salt were weighed and dissolved in an ethylene glycol solution in a molar ratio of 2:1 to form a Zn-Bi-O matrix solution; The obtained Zn-Bi-O matrix solution and Ba-Sr-O matrix solution are mixed uniformly, wherein the molar percentage of Zn-Bi-O matrix solution: Ba-Sr-O matrix solution = 1% to 50%: 1% to 50%, and stirred with a magnetic force and heated to 80 to 120° C. to form a uniform transparent solution 1, which is set aside; 3) Weigh 0.01-3 mol of tetrabutyl titanate and dissolve it in anhydrous ethanol, and drop 0.01-0.3 mol of acetylacetone into it, stir it thoroughly to form a uniform transparent yellow solution 2, and set it aside; 4) The transparent solution 1 obtained in step 2) and the transparent yellow solution 2 obtained in step 3) are mixed uniformly, a complexing agent is weighed and added to the mixed solution, and the mixture is stirred at a temperature of 80 to 120° C. until a (Zn-Bi-Ti-O)-(Ba-Sr-Ti-O)-based composite sol is formed, and an appropriate amount of dispersant is added to the composite sol for standby use; wherein the molar percentage of complexing agent: metal ion = 30% to 500%: 100% to 800%; 5) The La-Mn-O-based powder obtained in step 1) is ultrasonically dispersed for 50 to 150 minutes by an ultrasonic-assisted method, and a proper amount of dispersant is added thereto, and then added dropwise to the (Zn-Bi-Ti-O)-(Ba-Sr-Ti-O)-based composite sol in step 4), and stirring is continued for 3 to 6 hours. After the (Zn-Bi-Ti-O)-(Ba-Sr-Ti-O)-based composite sol is fully coated on the surface of the La-Mn-O-based powder to form a material with a core-shell structure, it is dried at a constant temperature of 170 to 250° C. for 25 to 45 hours to obtain a dry gel, wherein the molar percentage of each component is La-Mn-O:(Zn-Bi-Ti-O)-(Ba-Sr-Ti-O)=1% to 99%:99% to 1%; 6) Thermally decompose the dry gel obtained in step 5) at a temperature of 800-1000° C. for 5-8 hours to obtain a x% La-Mn-O@(100-x)% (Zn-Bi-Ti-O)-(Ba-Sr-Ti-O) composite core-shell structure powder material.
3. The preparation method according to claim 2, characterized in that: In step 1): a. Weigh analytically pure lanthanum salt and manganese salt as raw materials according to molar percentage, wherein the molar percentage of lanthanum salt: manganese salt = 4% to 100%: 4% to 100%, dissolve in deionized water to prepare a 0.04 to 3 mol / L ion mixed solution; b. Weigh a complexing agent and add it to the ion mixed solution of step a, wherein the molar percentage of complexing agent: metal ion = 30% to 500%: 100% to 800%; c. Stirring the mixed solution obtained in step b at 80-120° C. for 3-6 h to form a La-Mn-O-based sol, drying the sol at 170-250° C. for 25-45 h to obtain a xerogel, and grinding the xerogel for 5-8 h to obtain a powder; d. The powder obtained in step c is pre-calcined by thermal decomposition at a temperature of 600-1000° C. for 5-8 hours, and then taken out and ground for 5-8 hours to obtain La-Mn-O-based powder.
4. The preparation method according to claim 3, characterized in that: In step a), the lanthanum salt is lanthanum acetate, lanthanum nitrate or lanthanum oxalate, and the manganese salt is manganese acetate, manganese nitrate or manganese oxalate.
5. The preparation method according to claim 3, characterized in that: In step b), the complexing agent is citric acid, ethylenediaminetetraacetic acid, malic acid or malonic acid.
6. The preparation method according to claim 2, characterized in that: In step 2), the strontium salt is strontium acetate, strontium nitrate or strontium oxalate; and the barium salt is barium acetate, barium nitrate or barium oxalate.
7. The preparation method according to claim 2, characterized in that: In step 2), the bismuth salt is bismuth acetate, bismuth nitrate or bismuth oxalate; and the zinc salt is zinc acetate, zinc nitrate or zinc oxalate.
8. The preparation method according to claim 2, characterized in that: The complexing agent is citric acid or ethylenediaminetetraacetic acid or malic acid or malonic acid.
9. The preparation method according to claim 2, characterized in that: The dispersant is polyvinyl alcohol, polyacrylic acid or polyacrylamide.
Citation Information
Patent Citations
Double perovskite phase composite thermistor material with adjustable temperature range and B value and preparation method thereof
CN110423112A
Composite negative temperature coefficient heat-sensitive material with core-shell structure in ultra-wide temperature range and preparation method of composite negative temperature coefficient heat-sensitive material
CN114436334A
Semiconductor ceramic with negative resistance temperature coefficient and negative temperature coefficient thermistor
CN1348192A
Ceramic heating element
JP1998214674A